Short Communication: Inventory of native orchids in Makki Sub-District, Lanny Jaya, Papua, Indonesia - VERENA AGUSTINI; LISYE I. ZEBUA; NONANCE WENDA (Biodiversitas Journal of Biological Diversity, 2016)
Agustini V, Zebua L, Wenda N. 2016. Inventory of native orchids in Makki Sub-District, Lanny Jaya, Papua, Indonesia.Â Biodiversitas 17: 301-305. Orchids have been over exploitation since years ago. Some of orchids species are becoming threatened,Â endangered or even vanished that which may have not been found or discovered. Lanny Jaya, Papua, Indonesia is a new district locatedÂ at latitude 03oÂ 57â€™ 08â€ S and longitude 138oÂ 25â€™ 05.02â€ E, covers an area of 2.248 kmÂ 2. The establishment of this new district gives impactÂ to the plant habitat including orchids. The study was done in Makki Sub-District, Lanny Jaya, Papua, Indonesia. The present study is anÂ inventory orchid species in Lanny Jaya by explorative method. There were 22 species (17 genera) consist of epiphytic, terrestrial and lithophytic orchids. Among them Dendrobium subclausum is the most abundance species in this area. With the combination of bright orange and yellow colors in sepal it can be seen throughout the year.